Seroprevalence and Genetic Characterization of Toxoplasma gondii among Children with Neurodevelopmental Disorders in Egypt - Sara M. Elzeky; Nairmen Nabih; Aida A. Abdel-Magied; Dina S. Abdelmagid; Aya E. Handoussa; Marwa M. Hamouda (Journal of Tropical Medicine)
Toxoplasma gondii is a parasite with a special predilection for the central nervous system. Toxoplasmosis's contribution to the triggering of many neurodevelopmental disorders was established. This study aimed to detect the seroprevalence and genotypes of T. gondii strains in children with neurodevelopmental disorders. The study included 180 children with neurodevelopmental disorders and 180 children in the control group. Assessment of seropositivity of Toxoplasma IgM and IgG antibodies in patients and controls was carried out. Genetic characterization of T. gondii was obtained by nested polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) technique targeting dense granule gene (GRA6). Our results showed that the overall seroprevalence of T. gondii antibodies in the patient and controls was 35.6% and 11.7%, respectively. Nested PCR showed positivity in 11.1% of the patient group for T. gondii DNA. T. gondii seropositivity rate was significantly high in patients with hydrocephalus and also in patients with epilepsy. Positive nested PCR was significantly high in children with hydrocephalus only. Genotyping using nested PCR-RFLP showed genotype I (80%) followed by atypical strains (20%) with no association with any specific clinical presentation. In conclusion, among toxoplasmosis-positive children with neurodevelopmental disorders, analysis of T. gondii GRA6 locus revealed the predominance of type I genotype followed by atypical strains.